1991
DOI: 10.3758/bf03205998
|View full text |Cite
|
Sign up to set email alerts
|

The basis of the Bourdon illusion

Abstract: Day (1990) and Day, Mitchell;and Stecher (1990) Wenderoth, Criss, and van der Zwan (1990), Wenderoth and O'Connor (1987a, 1987b), and Wenderoth, O'Connor, and Johnson (1986 Day (1990) and Day et aL (i990).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It is important in this context that the illusions also occur when the two thin triangles are placed side by side with their edges parallel and at an angle with their edges at right angles (Wenderoth, 1991). These arrangements result in illusions of nonparallelness and nonright angularity, respectively (Day et aI., 1990).…”
Section: Discussionmentioning
confidence: 99%
“…It is important in this context that the illusions also occur when the two thin triangles are placed side by side with their edges parallel and at an angle with their edges at right angles (Wenderoth, 1991). These arrangements result in illusions of nonparallelness and nonright angularity, respectively (Day et aI., 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Wenderoth and O'Connor (1987b) reported that no such second-stage adjustment occurred with truly bent edges. Wenderoth (1990) has proposed that this second-stage adjustment reflects the position effect that can be seen in Figure IA; even were the upper and lower chevron segments set parallel to the adjacent wedge edges, more global inspection of the whole Bourdon figure gives the clear impression that the left-hand upper and lower extremities (i.e., the left edges of the wedge bases) are displaced to the right of the central apices. Thus, in Figure lA, attraction orientation effects and position effects occur in the same direction and reinforce each other.…”
Section: Discussionmentioning
confidence: 99%
“…To measure the effect, Wenderoth, O'Connor, and Johnson (1986a) and Wenderoth andO'Connor (1987a, 1987b) had subjects set a variable chevron, represented by the straight line in Figure lA, to match the apparent bend. When the truly straight edge of the solid Bourdon figure was oriented 22.5°clockwise and each vertex anThis research was supported by Australian Research Council Grant A7883l87l to the first author.…”
mentioning
confidence: 99%
“…According to another explanation put forward by Wenderoth et al (1986) (see also Wenderoth, 1991), every stimulus is processed along three separate neural channels coding orientation, position, and collinearity. These authors postulated that the illusion arises from conflicting signals between these channels.…”
Section: Previous Explanations For the Bourdon Illusionmentioning
confidence: 99%